Penguatan Desain Kemasan Pupuk Kotoran Sapi dalam upaya Pemberdayaan Kelompok Tani “Dewi Sri”: Strengthening the Design of Cow Manure Fertilizer Packaging to Empower The "Dewi Sri" Farmer Groups - Wijaya, Muhammad Burhan Rubai; Damayanti, Astrilia; Kurniawan, Adhetya; Wibowo, Muhammad Yusuf; Ar Rasyid, Moh. Rizal; Salwa, Dian Fatimatus; Fitri, Amelia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The “Dewi Sri” Farmers Group is located in Terwidi Hamlet in Plalangan Village, Gunungpati, Semarang City, where part of the population raises various livestock, namely cows, goats and poultry. The problem that occurs is the accumulation of cow dung which causes environmental pollution. This service activity aims to overcome the buildup of livestock waste, especially cow manure by using it as organic fertilizer and then packaging it with an attractive design so that it has a high selling value. The methods used are preparation, socialization, and mentoring. The results obtained from this activity, the preparation/coordination stage with the head of KT Dewi Sri, the socialization stage in the form of an explanation of the innovative packaging design, and the mentoring stage in the form of the issuance of a Packaging Design Copyright by the Directorate General of Intellectual Property.